Managerial Accounting - Garrison, Ray H.; Noreen, Eric W. (USA McGraw-Hill Irwin, 2000)
As the long-time best-seller, Garrison has helped guide close to 3 million students through managerial accounting since it was first published. It identifies the three functions managers must perform within their organizations-plan operations, control activities, and make decisions-and explains what accounting information is necessary for these functions, how to collect it, and how to interpret it. Garrison's Managerial Accounting, is known for its accuracy and rigor. It is also unique in that the authors write the most important supplements that accompany the book: solutions manual, test bank, instructor's manual, and study guide.
Donated by: Anvar Hodjaev
Keywords: Managerial accounting